2007
DOI: 10.1021/jf071132f
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Anthocyanins and Pyranoanthocyanins. Studies on Aromatic Hydrogen–Deuterium Exchange Reactions in Methanol

Abstract: Reactivity studies involving anthocyanin structures and their equilibrium forms will lead to better understanding of the properties of these antioxidants. Hydrogen-deuterium (H --> D) exchange reactions at various sites of the 3-glucosides of delphinidin (1), petunidin (2), malvidin (3), and the corresponding 3-glucosides of carboxypyranodelphinidin (4), carboxypyranopetunidin (5), carboxypyranomalvidin (6), and the flavonol quercetin 3-O-(6-alpha-rhamnopyranosyl-beta-glucopyranoside)(7) have been examined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
(69 reference statements)
1
20
0
2
Order By: Relevance
“…This suggestion was further supported by the absence of the STD signals of the Ha protons at 3.3 and 3.7 ppm. Finally, the decreased STD signal of proton H–8 of 3′ quercetin‐alanine is attributed to the hydrogen‐deuterium (H → D) exchange effect that has been previously reported .…”
Section: Resultssupporting
confidence: 68%
“…This suggestion was further supported by the absence of the STD signals of the Ha protons at 3.3 and 3.7 ppm. Finally, the decreased STD signal of proton H–8 of 3′ quercetin‐alanine is attributed to the hydrogen‐deuterium (H → D) exchange effect that has been previously reported .…”
Section: Resultssupporting
confidence: 68%
“…The data fitting of the relative integrations of these proton resonances follows first-order kinetics as reported. 30 The exchange rate constants (k) deduced in Figure 2 show an obvious order of H-2,6> H-4 for each isomer. Besides, the exchange rates of trans-isomer are much larger than those of cis-isomer, which means the former undergoes faster H/D exchange.…”
Section: Resultsmentioning
confidence: 94%
“…Since the exchange reactivity is mainly determined by the first step, the carbon atom which is more negatively charged would be more susceptible for attack by the deuterium atom. 30,35 In addition, it was found that the negatively charged oxygen-substitute group on aromatic ring is expected to stabilize the σ-complex intermediate, 35 and consequently results in the increase of exchange reactivity. This In previous studies on H/D exchange of polyphenol, the site in the middle of two meta hydroxyl group seems to have priority of exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1315,31 Under acidic conditions (e.g., CF 3 COOD), H/D exchange reactions of phenolic hydrogens occur rapidly, over seconds to minutes, via keto–enol tautomerization or electrophilic-substitution reaction. 3133 On the other hand, under neutral conditions, H/D exchange takes from several hours to days (S12, Supporting Information), 14,34 and recent evidence shows that amines (e.g., [hydroxy-]lysine in collagen) can facilitate deuteration under very mild conditions. 35 In the present study, the H/D exchange process of 1 dissolved in CD 3 OD could be followed over time in the 1D NMR spectra.…”
Section: Resultsmentioning
confidence: 99%